The use and impact of fast-track departures: exploring prosecutorial and judicial discretion in federal immigration cases - Tillyer, Rob (Crime & delinquency, 2016)
Fast-track programs allow prosecutors in authorized jurisdictions to expedite case processing for offenders charged with immigration violations. We explore whether disparities from fast-track usage exist by utilizing multilevel modeling techniques to analyze 2008 United States Sentencing Commission data on the federal sentencing of illegal entry defendants. Results indicate that the use of fast-track programs, the amount of sentence reduction applied in fast-track cases, and the overall sentence length is differentially impacted by various legal, extralegal, case processing, and district-level variables. These findings suggest some support for previous theoretical explanations for decision-making, but also indicate that these processes may differ slightly in the context of fast-track programs.